2019
DOI: 10.1055/a-0839-4514
|View full text |Cite
|
Sign up to set email alerts
|

Even non-experts identify non-dysplastic lesions in inflammatory bowel disease via chromoendoscopy: results of a screening program in real-life

Abstract: Background and study aims Chromoendoscopy with targeted biopsy is the technique of choice for colorectal cancer screening in longstanding inflammatory bowel disease. We aimed to analyze results of a chromoendoscopy screening program and to assess the possibility of identifying low-risk dysplastic lesions by their endoscopic appearance in order to avoid histological analysis. Materials and methods We retrospectively reviewed chromoendoscopies performed between February 2011 and June 2017 in seven Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Sensitivity, specificity, positive and negative likelihood ratios with the Kudo classification were 91 %, 76 %, 3.8, and 0.12, respectively. Recently Aladrén et al aimed to analyze results of a CE screening program in Spain and to assess the possibility of identifying low risk dysplastic lesions by their endoscopic appearance, in order to avoid histological analysis [100]. Correlation between dysplasia and Kudo pit pattern predictors of dysplasia (Kudo ≥ III) was low while Kudo I and II lesions were correctly identified with a high negative predictive value of 92 %, even by nonexperts.…”
Section: Statementmentioning
confidence: 99%
“…Sensitivity, specificity, positive and negative likelihood ratios with the Kudo classification were 91 %, 76 %, 3.8, and 0.12, respectively. Recently Aladrén et al aimed to analyze results of a CE screening program in Spain and to assess the possibility of identifying low risk dysplastic lesions by their endoscopic appearance, in order to avoid histological analysis [100]. Correlation between dysplasia and Kudo pit pattern predictors of dysplasia (Kudo ≥ III) was low while Kudo I and II lesions were correctly identified with a high negative predictive value of 92 %, even by nonexperts.…”
Section: Statementmentioning
confidence: 99%
“…Twenty-four studies reported the use of Kudo classification for lesion characterization in IBD (predominantly patients with UC). 6,7,1216,20,22,23,28,31,3338,4042,4446 Eighteen studies used DCE (IC: 13, MB: 5, CV: 6), whereas 11 studies used VCE (NBI: 7, FICE: 2, i-SCAN: 2); magnification was used in 17 studies, and HD in 19 studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Another study using 769 stereomicroscopic pictures (509 neoplastic and 260 non-neoplastic) obtained from surgically resected specimens showed that pit pattern types III-V were significantly associated with the presence of neoplasia (sensitivity 77.4% and specificity 89.5%)[ 12 ]. Further, previous studies also demonstrated that pit pattern types I-II had a high negative predictive value to rule out the diagnosis of neoplasia (Table 1 )[ 13 , 14 ]. The findings in all of these studies suggest that magnifying endoscopy assessing Kudo pit patterns may be useful to differentiate between neoplastic lesions and non-neoplastic lesions in IBD patients.…”
Section: Utility Of Magnifing Chromoendoscopy For Ibdmentioning
confidence: 86%
“…Indeed, histopathological findings of regenerative mucosa can masquerade as dysplastic findings and make the diagnosis of dysplasia equivocal[ 16 ]. Several studies have also suggested that the correlation between dysplasia and pit pattern types III-V was low (Table 1 )[ 13 , 14 ]. Moreover, Kudo’s pit patterns cannot necessarily classify all of the findings which are observed in the neoplastic lesions in UC patients.…”
Section: Utility Of Magnifing Chromoendoscopy For Ibdmentioning
confidence: 99%